Molecular Divergence and Phylogenetic Positioning in Siluriformes Species Using mtDNA COI Gene - Imran, Mohd (Asian Journal of Biological and Life Sciences)
Aim: Molecular divergence between species or a group of species is efficient tool to trace the relation between them and assist in their better phylogenetic positioning with good bootstrap supports. The study has emphasised on a chosen group of siluriformes species available in the nearest water resource which includes species from family Clariidae, Heteropneustidae, Bagridae, and Siluridae. Materials and Methods: Standard barcoding protocol was followed where the intraspecific and interspecific pair wise sequence divergences were calculated based on Kimura-2- Parameter model, followed by phylogenetic tree clustering. Results: A considerable gap was found in the divergence values between species which is sufficient to differentiate and delimit them. For intraspecific divergence, the average was found less than 1% whilst the interspecific divergence varied from 16 to 24%. When the comparison was made on an average basis, the divergence between species (20.40%) was found approx. 25 times higher than intraspecific divergence (0.811%). When the divergence was calculated separately at each codon position, the maximum contribution was found from 3rd codon position (78.4%) to the combined divergence which was followed by 1st codon position (6.87%) and the least contribution from 2nd codon position (1.82%). The clustering analysis with Neighbor-Joining and Maximum likelihood methods delimit the species with parallel phylogenetic clustering supporting the divergence trends. Conclusion: The work provides a thorough picture of the relationship between divergence values and how this gap in divergence values plays a critical role in differentiating species while at the same time assisting in deciphering their taxonomic and phylogenetic positioning.
Keywords: Molecular divergence; Phylogenetic clustering; Siluriformes